Enhancing EFL Students’ Writing Skills in Recount Texts through Scrapbook Activities - Palupi, Dinar Prasetyaning; Santoso, Dian Rahma (PROJECT (Professional Journal of English Education), 2025)
This study discusses the implementation of a scrapbook for improving writing skills to the eighth grade students junior high school in Sidoarjo district. This study aimed to determine how using scrapbooks affects students’ writing skills in recount text. This study used quantitative approach with pre-experimental design using one class. The instrument used in this study was a writing test with 25 participants. The data were obtained from the pre-test and post-test result. The sample T-test result with SPSS shows a significant difference between the pre-test and post-test.  The average score for the pre-test was (47.3). Meanwhile, the average score of the post-test was (58.9). It shows that there are differences in the score results. The means of the post-test score is higher than that of the pre-test. Based on the paired sample test, the T-test results revealed that sig. (2-tailed) was 0.000, while alpha (α) was 0.05 (0.000<0.05). This indicates that H0 is rejected and Ha  is accepted. The results show that scrapbook media significantly affects teaching students how to write the recount texts.